Clinical Efficacy of Carvedilol In Treatment of Patients With Ischemic Heart Disease and Chronic Heart Failure (Cardiovascular Journal, 2011)
Background: In the pathogenesis of CHF neurohormonal changes, in particular, changes of activity of sympathetic nervous system (SNS) occupies an important position. For this reason, researchers concentrated on the use β-blockers in therapy of patients with CHF. They reduce heart rate, improve diastolic function of the myocardium, reduce secretion of renin and restore the sensitivity of β- adrenoreceptors to its regulatory influences. We studied the influence of the 3rdgeneration betaadrenoblocker – Carvedilol in patients with CHF- including clinical efficacy and reduction of oxidative stress. Methods: The study was conducted in Saint-Petersburg State Medical University, from January 2000 to June 2000. 37 patients (33 male and 4 female) with CHF class III or IV despite receiving standard therapy of heart failure were enrolled in the study for the treatment with Carvedilol. All of the patients received Carvedilol for 6 months at a dose of 12.5-50mg/day with standard therapy of Heart Failure, which was not changed during next 6 months. Results: The average age of the patients was 56.8±2.3 years. The cause of CHF was IHD. 34 patients had chronic stable angina (CCS class II-IV). The majority of the patients had a history of myocardial infarction (91.8%); of these 73.5% of the patients had a history of repeated MI. Hypertension stage 2 and 3 was associated in 32.4% patients.Long-term therapy with Carvedilol led to improvement of the clinical status of the patients. After 6 months therapy with Carvedilol frequency of hospitalization was significantly reduced (1.36±0.23 vs. 0.33±0.1; p